1988
DOI: 10.1017/s0021932000006684
|View full text |Cite
|
Sign up to set email alerts
|

Changing Determinants of Infant and Child Mortality: On the Basis of the Korean Experience, 1955–73

Abstract: From analysis of the 1974 Korean National Fertility Survey data, the changing patterns of demographic and socioeconomic determinants of infant and child mortality are generalized. The pattern for infant mortality is:(1) in a traditional society demographic factors affect infant mortality more than socioeconomic factors; (2) at the early stage of development, demographic factors are replaced by socioeconomic factors as the main determinants; (3) when the difference in living standards between social classes nar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

1991
1991
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 7 publications
0
6
0
1
Order By: Relevance
“…We also have evidence for educational differentials in adult mortality and maternal educational differentials in child mortality in South Korea (Choe 1987;Kim 1988;Kim 2004). Hence, improvements in educational attainment should increase the number of survivors in old age and the number of surviving offspring.…”
Section: Differential Mortalitymentioning
confidence: 80%
See 1 more Smart Citation
“…We also have evidence for educational differentials in adult mortality and maternal educational differentials in child mortality in South Korea (Choe 1987;Kim 1988;Kim 2004). Hence, improvements in educational attainment should increase the number of survivors in old age and the number of surviving offspring.…”
Section: Differential Mortalitymentioning
confidence: 80%
“…The survey collected information on the total number of surviving children only rather than the number of total births. Because child mortality is negatively associated with maternal education in South Korea (Choe 1987;Kim 1988), using the number of surviving children would underestimate the educational differentials in fertility and sibship size. However, mortality rates among children and young adults are fairly low in South Korea (Kim 2004), suggesting that this data limitation will not seriously bias our results.…”
Section: Datamentioning
confidence: 99%
“…The relative importance of socioeconomic and demographic factors on infant mortality, however, varies with the level of socioeconomic development of the nation. Kim (1988) observed that in a traditional society, demographic factors affect infant mortality more than the socioeconomic factors. In the early stages of development, demographic factors are replaced by socioeconomic factors, and in the later stages the effect of demographic factors becomes very small.…”
Section: Introductionmentioning
confidence: 99%
“…Given the negative association between maternal education and child mortality in South Korea (Choe, 1987; Kim, 1988), using the number of surviving children would underestimate the educational differentials in fertility. This underestimation has two implications for the present analysis.…”
Section: Datamentioning
confidence: 99%